KAJIAN PEMANFAATAN TEKNOLOGI INFORMASI PADA BIDANG PERTANIAN MENUNJANG PEMBANGUNAN YANG BERKELANJUTAN - Didik Nugroho; Sri Siswanti (STMIK Sinar Nusantara, 2015)
Agriculture is an important factor supporting the resilience of a nation. Advanced agriculture will assist the state in maintaining the ability to meet the needs food for its citizens. Furthermore agriculture results can also be sold to. Agricultural progress apart from planting process factors must also be supported by information and good management processes. The process requires data management. Data processing technology currently using Information Technology. This study examines the application of information technology in libraries in Indonesia in the field of agriculture. References taken from the material functions and benefits technology information on the community and on the material needs of the data in the process of agriculture . The two topics of the library to the application of technology formulated Information in agriculture. The results of the research library for the application of information technologies used for dissemination of information, learning and counseling, process analyst, process coordination and management of agricultural management Keywords: Information Technology, the Management, Learning and Counseling, management of agriculture.